LEVERAGING SOCIAL MEDIA AS A PARTICIPATORY PLATFORM FOR ECOTOURISM DEVELOPMENT: A CASE STUDY OF SITU CISANTI - Anwar, Rully Khairul; Khadijah, Ute Lies Siti; Kusmayadi, Ika Merdekawati (Sosiohumaniora, 2025)
Governments in developing countries view ecotourism as a strategy to enhance local income and improve community livelihoods. However, the dominance of mass tourism systems often constrains the potential benefits of ecotourism for local communities. This study aims to examine the forms and dynamics of community participation in ecotourism development at Situ Cisanti, Tarumajaya Village, Kertasari Subdistrict, Bandung Regency, West Java, Indonesia. The research employs a qualitative case study approach informed by critical theory. Data collection include field observations, in-depth interviews with local community members, tourism stakeholders, and government officials, as well as document analysis. The findings identify four main forms of community participation: environmental protection, local entrepreneurship, cultural preservation, and ecotourism marketing. Social media functions as a participatory platform that facilitates information dissemination, stakeholder collaboration, and community empowerment through the Community Information Group (Kelompok Informasi Masyarakat/KIM). Nevertheless, participation remains largely tokenistic, as community members tend to follow externally driven agendas without possessing significant decision-making authority. This study highlights that social media has the potential to enhance local contributions to ecotourism development when integrated with inclusive government policies and community capacity-building initiatives.